Colonization with third-generation cephalosporin-resistant Enterobacteriaceae on hospital admission: prevalence and risk factors - Axel Hamprecht; Anna M. Rohde; Michael Behnke; Susanne Feihl; Petra Gastmeier; Friedemann Gebhardt; Winfried V. Kern; Johannes K.‐M. Knobloch; Alexander Mischnik; Birgit Obermann; Christiane Querbach; Silke Peter; et al. (2016)
The objectives of this study were to prospectively assess the rectal carriage rate of third-generation cephalosporin-resistant Enterobacteriaceae (3GCREB) in non-ICU patients on hospital admission and to investigate resistance mechanisms and risk factors for carriage. Adult patients were screened for 3GCREB carriage at six German tertiary care hospitals in 2014 using rectal swabs or stool samples. 3GCREB isolates were characterized by phenotypic and molecular methods. Each patient answered a questionnaire about potential risk factors for colonization with MDR organisms (MDROs). Univariable and multivariable risk factor analyses were performed to identify factors associated with 3GCREB carriage. Of 4376 patients, 416 (9.5%) were 3GCREB carriers. Escherichia coli was the predominant species (79.1%). ESBLs of the CTX-M-1 group (67.3%) and the CTX-M-9 group (16.8%) were the most frequent β-lactamases. Five patients (0.11%) were colonized with carbapenemase-producing Enterobacteriaceae. The following risk factors were significantly associated with 3GCREB colonization in the multivariable analysis (P < 0.05): centre; previous MDRO colonization (OR = 2.12); antibiotic use within the previous 6 months (OR = 2.09); travel outside Europe (OR = 2.24); stay in a long-term care facility (OR = 1.33); and treatment of gastroesophageal reflux disease (GERD) (OR = 1.22). To our knowledge, this is the largest admission prevalence study of 3GCREB in Europe. The observed prevalence of 9.5% 3GCREB carriage was higher than previously reported and differed significantly among centres. In addition to previously identified risk factors, the treatment of GERD proved to be an independent risk factor for 3GCREB colonization.